Mental impact of the training associated with physical exercise and skills in learning transmissions defense skill in the game of volleyball - gane, saead (Journal of Physical Education, 2010)
Training is a mental one of the basic methods for the preparation of Mathematical physical and Mharria which accompanied the educational process and one of the most practical ways in which aims to link the mental picture of the stages of the movement and the true picture it, has addressed many of the studies the issue of training of mental and found the relationship between the performance skills of the athlete and the extent of integration of these skill in the mental image, which should include all aspects of mobility to complement this picture, for this philosophy is accompanying physical exercise and skills training with mentally believe that it contributes to increase the speed of performance development, hence evident importance of the study that training mental contribute to further improve feedback from sources external by watching a player of the form to the internal feedback, the goal is to control the ideas Fezla skill for installation in memory and motor speed in the development of locomotor performance and its access to the best level of performance skill.The research aims to the following:1. Development of educational modules for exercise and skills associated with mental training during the units receiving transmissions of skill in the game of volleyball.2. Knowledge of the impact of these educational units accompanied by mental training with physical exercise in learning the skill to receive transmissions for the game of volleyball.The research was imposed as follows: 1. There are significant differences between the results of tests befor-and-after for the two experimental and control group in learning the skill of the reception and for a posteriori tests.2. There are significant differences between the results of a posteriori tests for the experimental group using the mental training associated with physical exercise and skills to learn a skill to receive transmissions in the game of volleyball.The researcher used the experimental design groups equal random, so as to appropriateness of the nature of the problem, were selected (10) players from the second stage students in the College of Physical Education / University of Maysan sample to search randomly were divided into two groups by experimental group and a control group and the number of each group (5) players, as the first experimental group practiced exercises designed to accompany training for mental exercise, skill, while the control group, leads you exercises and techniques are followed by a teacher thermoplastic material.Total number of units for each group (12) educational unit was a single educational unit time (90) minutes and one and a half has been implemented and the application modules in the hall of the Faculty of Physical Education by two units a week. The findings as following :1. The existence of significant differences between pre and post tests and post tests in favor of the group that practiced mental training, training associated with the skills in learning a skill reception.2. The use of mental training associated with the exercise skill has a positive impact and effective in learning the skill to receive transmissions in volleyball. Recommendations :1. emphasis on mental training to use when learning the basic skills in the game of volleyball.2. The need to use the player form when teaching basic skills in a game of volleyball for the proper functioning watch . 3. the need to give the learner time to organize the error and corrected for the movements of multiple responses by thinking Kngvep due considering that the rapid movements need to act simultaneously in an awkward position.